1999
DOI: 10.3109/09513599909167563
|View full text |Cite
|
Sign up to set email alerts
|

Raloxifene analog LY 117018 effects on central and peripheral β-endorphin

Abstract: Raloxifene is a selective estrogen receptor modulator with a benzothiophene structure, that exerts an estrogen-like action on some target tissues and an anti-estrogenic action on the uterus and breasts. A limited number of data are available on the effect of raloxifene on neuroendocrine function. Since beta-endorphin (beta-EP) is considered a marker of neuroendocrine function, the aim of the present study was to evaluate the effects of a 14 day treatment with a raloxifene analog, LY 117018, on beta-EP content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 30 publications
3
19
0
Order By: Relevance
“…We suggest that the increase of bendorphin tone, observed by Genazzani et al (17) in rats, but above all by Florio et al (18) in postmenopausal raloxifene-treated women, could reduce PRL synthesis and secretion. On the contrary, the increase of opiatergic tone could exert a minor role on gonadotropin secretion, because of the prevalent stimulatory effect of hypoestrogenemia.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…We suggest that the increase of bendorphin tone, observed by Genazzani et al (17) in rats, but above all by Florio et al (18) in postmenopausal raloxifene-treated women, could reduce PRL synthesis and secretion. On the contrary, the increase of opiatergic tone could exert a minor role on gonadotropin secretion, because of the prevalent stimulatory effect of hypoestrogenemia.…”
Section: Discussionmentioning
confidence: 46%
“…In premenopausal women, Baker et al (9) showed that raloxifene increases serum FSH and E2 levels, and reduces PRL concentrations by 10 -35% of basal values. Studies performed in ovariectomized rats which had not undergone estrogen replacement therapy suggested that raloxifene can play an estrogen-like action on neuroendocrine opiatergic pathways, increasing b-endorphin concentrations in the anterior and neurointermediate pituitary lobe and in the hypothalamus (17). These data were recently confirmed also in postmenopausal women, in whom the administration of raloxifene 60 mg/day significantly increased circulating b-endorphin levels after 3 and 6 months of treatment (18).…”
Section: Discussionmentioning
confidence: 87%
“…Interesting data have recently been reported concerning the effects of the raloxifene analog LY-117018 on β-endorphin content in various rat organs [35]. This compound has been shown to act on central and peripheral β-endorphin levels via an estrogen-like mechanism in OVX rats, thus increasing β-endorphin levels in pituitary, hypothalamus, and plasma.…”
Section: Discussionmentioning
confidence: 99%
“…This compound has been shown to act on central and peripheral β-endorphin levels via an estrogen-like mechanism in OVX rats, thus increasing β-endorphin levels in pituitary, hypothalamus, and plasma. On the contrary, LY-117018 shows a clear antiestrogenic effect on β-endorphin levels both in fertile animals and in OVX rats treated with 17β-E2 [35]. These data suggest that LY-117018 has a different influence on the opioidergic pathways, depending upon the presence or absence of endogenous or exogenous estradiol.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, tamoxifen was also shown to block the effect of estradiol on dendritic spines of hippocampal neurons (Murphy and Segal 1996). The raloxifene analogue LY117018 has an estrogen-like action on neuroendocrine opiatergic pathways when administered alone in ovariectomized rats, whereas it exerts an anti-estrogenic effect in fertile or ovariectomized rats treated with 17␤-estradiol (Genazzani et al 1999).…”
Section: Nmda Receptors Mrna Levelsmentioning
confidence: 99%